Trends and Research Issues of Augmented Reality in Education: A Bibliometric Study - Gema Rullyana; Rizki Triandari (Jurnal Teknologi Pendidikan, 2024)
This study aims to comprehensively review Augmented Reality (AR) research in education through a bibliometric analysis of 1,850 journal articles and proceedings published between 2015 and 2023. Data were obtained from the Scopus database, which focused on social science subjects. This study focuses on two main aspects: performance analysis and science mapping. The results show a consistent upward trend in AR research, with the United States leading the number of publications, followed by China, Spain, Taiwan, and Turkey. The most influential authors are Akçayır, M. and Akçayır, G., with the highest number of citations. Visualization using VOSviewer yielded seven research clusters, highlighting the role of AR and VR in interactive teaching, simulation, and engineering education. The findings also suggest further research opportunities in the areas of "nursing education," "simulation," and "educational innovation," affirming AR's potential for innovative and sustainable learning. This research contributes to the understanding of the development of AR in education and serves as a useful reference for other researchers interested in studying AR in education.